2009
DOI: 10.2214/ajr.07.3107
|View full text |Cite
|
Sign up to set email alerts
|

Prepatellar Quadriceps Continuation: MRI of Cadavers with Gross Anatomic and Histologic Correlation

Abstract: The prepatellar quadriceps continuation is formed by fibers of the rectus femoris tendon and connects the quadriceps and patellar tendons. All tendons are attached through formation of a chondroapophyseal zone and are therefore transformed into a seam of fibrocartilage. Based on these anatomic features, separation of the prepatellar quadriceps continuation from the patella in the absence of more extensive abnormalities of the quadriceps mechanism is plausible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 11 publications
0
25
0
2
Order By: Relevance
“…We hypothesize that the anatomy of the quadriceps enthesis may have influenced the morphology of this fracture. The quadriceps entheseal zone does not stop at the upper pole; it continues though the anterior margin of the patella, as does the quadriceps patellar continuation [14]. The mechanism of injury in our case involved a forceful contraction of the quadriceps muscle with the knee in hyperextension.…”
Section: Discussionmentioning
confidence: 64%
“…We hypothesize that the anatomy of the quadriceps enthesis may have influenced the morphology of this fracture. The quadriceps entheseal zone does not stop at the upper pole; it continues though the anterior margin of the patella, as does the quadriceps patellar continuation [14]. The mechanism of injury in our case involved a forceful contraction of the quadriceps muscle with the knee in hyperextension.…”
Section: Discussionmentioning
confidence: 64%
“…This layer partially adheres to the periosteum of the patella and partially continues into the crural fascia. Wangwinyuvirat et al (2009) found that at the proximal pole of the patella the entire quadriceps tendon had an average thickness of 8.54 mm, but only a percentage of these fibres (7.87 mm) insert into the proximal patellar pole, while some fibres (0.68 mm) pass over the anterior patellar surface. Histological analysis showed that the fibres that continue over the patella were the distal extensions of the longitudinal fibres of the rectus femoris tendon.…”
Section: Clinical Pearl 85 Iliotibial Band Syndromementioning
confidence: 98%
“…All four components, namely rectus femoris, vastus lateralis, vastus medialis and vastus intermedius, converge to form the quadriceps tendon. However, anatomical studies have shown that each of these layers may potentially terminate in a separate aponeurotic layer [2,4,5]. In one anatomic study, investigators showed a trilaminar arrangement of fibrous tissue structures anterior to the patella that included a superficial transverse fascial layer, intermediate oblique aponeurotic layer, and longitudinally oriented deep layer of fibers of the rectus femoris [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, anatomical studies have shown that each of these layers may potentially terminate in a separate aponeurotic layer [2,4,5]. In one anatomic study, investigators showed a trilaminar arrangement of fibrous tissue structures anterior to the patella that included a superficial transverse fascial layer, intermediate oblique aponeurotic layer, and longitudinally oriented deep layer of fibers of the rectus femoris [5,6]. Wangwinyuvirat et al in a cadaveric study of knee specimens described this deepest soft tissue layer, related to the deep rectus femoris tendinous fibers, as the "prepatellar quadriceps continuation" [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation